Jack Strong takes a stand - Greenwald, Tom (Greenwald, Tom. Charlie Joe Jackson book., 2015)
Tired of being forced to participate in sports and take extra lessons and tutoring to become well-rounded in anticipation of college, middle-schooler Jack Strong stages a sit-in on his couch until his parents ease up.